(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
Various nutritional disorders can cause the development of certain diseases and, in turn, contribute to premature aging of the body. Persons in boarding houses for the disabled deserve special attention. Such institutions in Uzbekistan are called “Sakhovat” boarding houses. The study involved 302 respondents over 60 years of age, including 136 (54.0%) men and 116 (46.0%) women. Of these, 59.1% were elderly, 38.0% were senile, and 2.9% were long-livers; the average age was 71 ± 0.40 years. For the purpose of nutritional assessment of diets and nutritional health risk factors, we studied 2,500 menu layouts of Sakhovat boarding schools according to 26 indicators. An analysis of the functional state of the chewing function of those cared for in nursing homes also shows a 100% need for easily digestible dietary food. It was found that 58.3% of those under care need diet No. 10 according to the Pevzner system, 47.2% in diet No. 9, 43.7% in diet No. 1, 30.1% in diet No. 2, 26.15% in diet No. 5, 22.2% in diet No. 7. There are errors in catering such as the replacement of butter with spreads, the predominance of flour and pasta, and the low content of vegetables and fruits. A nutritional assessment of the average daily diet of those under care showed a fairly high energy value (3513±43 kcal), a high level of total proteins 144.3±11 g, carbohydrates 515.4±22 g, a deficiency of fats of plant origin, proteins of animal origin, vitamins C, A, B6 0, B12, E.